FM Help Desk: user complaint system as an FM approach for facilities management services in Universiti Tun Hussein Onn Malaysia (UTHM) - Shafie, Fazira (2013)
An efficient and effective facilities management contributes to the productivity of an organisation in achieving its core activities. Higher educational institutions (HEIs), with teaching and learning as their core activities, have several physical and nonphysical facilities to manage. In reality, this involves with complex challenges in meeting the needs and demands of dynamic and demanding stakeholders. Therefore, a mechanism must be identified and developed to meet their demands. Facility management (FM) help desk has been identified as an online system for the university community to channel any complaints about the university facilities. This system is able to handle the complaints by managing, recording and maintaining them in a systematic and effective manner. Through this system, complaints should be resolved within one day, three days or seven days depending on the degree of urgency of the cases. This research focuses on how the FM help desk system can help the university to manage its facilities and to determine FM satisfaction indicators for facilities management services delivered through the FM help desk system. This research also suggested the improvement of this system based on the FM satisfaction indicators. Mixed method was used in this research. Via quantitative approach, 317 sets of questionnaires were distributed to respondents representing various levels of the university staff. Semi-structured interview technique focusing on the officers who directly involved in the management of university facilities, on the other hand, was carried out to obtain qualitative data. The results showed that the majority of users were satisfied with the implementation of FM help desk system as a user complaint system to improve the efficiency of the university facilities management. Furthermore, it has been suggested that this system can be improved based on the FM satisfaction indicators i.e., people, IT and technology, place and process. Thus, FM help desk system has been identified as an important mechanism in enhancing the management of complaints towards a better implementation of a quality facilities management system in the university.